Learning with Peers: Exploring the Experiences of University Students - Dubey, Alok (Voices of Teachers and Teacher Educators, 2019)
This article documents the challenges experienced in exploring the perceptions of quality education held by parents from different backgrounds. My respondents were parents (mostly mothers) of children studying in very different kinds of schools, namely a state government school, a central government school, a low fee charging private school and a high fee charging private school. The process of conducting interviews made me aware of some important considerations that make the voices of the parents from different backgrounds more accessible. I also realised the importance of language, transcription and translation in research methodologies and how these decisions taken in context of this specific research helped in bringing out authentic voices.